2015
DOI: 10.2147/tacg.s51484
|View full text |Cite
|
Sign up to set email alerts
|

The genetic basis of familial adenomatous polyposis and its implications for clinical practice and risk management

Abstract: Familial adenomatous polyposis (FAP) is an inherited disorder that represents the most common gastrointestinal polyposis syndrome. Germline mutations in the APC gene were initially identified as responsible for FAP, and later, several studies have also implicated the MUTYH gene as responsible for this disease, usually referred to as MUTYH-associated polyposis (MAP). FAP and MAP are characterized by the early onset of multiple adenomatous colorectal polyps, a high lifetime risk of colorectal cancer (CRC), and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 92 publications
4
59
0
5
Order By: Relevance
“…The site of germline mutation in the APC gene is known to correlate with the disease phenotype [1]. Our family 42 with pseudoexon 6/7 was associated with classical FAP in agreement with genotype-phenotype expectations.…”
Section: Discussionsupporting
confidence: 87%
“…The site of germline mutation in the APC gene is known to correlate with the disease phenotype [1]. Our family 42 with pseudoexon 6/7 was associated with classical FAP in agreement with genotype-phenotype expectations.…”
Section: Discussionsupporting
confidence: 87%
“…FAP is an autosomal dominant polyposis syndrome characterized by hundreds of adenomas in the large intestine as well as in the upper gastrointestinal tract (Leoz et al 2015, Waller et al 2016. It is due to germline mutations in APC gene located on long (q) arm of chromosome 5 at position 22.2.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Apart from colorectal cancer, patients with Gardner syndrome most often have small bowel cancer. The other cancers included pancreatic (Leoz et al 2015). Type 2 Turcot's syndrome is a very rare form of mutation of APC gene in which there is an association of intestinal polyposis and brain tumours -most often medulloblastoma (Gadish et al 2005, Skomorowski et al 2012.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Given the extent of his polyposis, the patient was advised to undergo definitive surgical management; he ultimately underwent total colectomy 8 months following his initial presentation. Subsequent genetic testing revealed that the patient was positive for the mutated APC gene thereby confirming the diagnosis of FAP [23]. …”
Section: Case Presentationmentioning
confidence: 99%